A process for change: The safe system approach and Vision Zero - Schell, William J.; Ward, Nicholas J. (Frontiers in Future Transportation, 2022)
While vision zero has been widely accepted as a core goal of many transportation agencies, to date efforts to achieve this target provide mixed results. One path to improved performance is gaining more interest in the United States-the safe system approach. While a safe system approach has proven successful in other countries and has great potential in the United States, successfully using this method requires a significant paradigm shift. Specifically, for many stakeholder organizations, establishing the safe system approach to reach Vision Zero represents a fundamental change in how they 1) perceive the road transport system, 2) interpret their role in that system, 3) operate with other system elements (stakeholder organizations), and 4) define a vision of success for the system. This level of transformative change requires structured preparation and deliberate management of the change process to be successful. In this paper we present a perspective on a process to initiate and manage this change that can increase the odds of success.